Who calls the African Wild Dog? - Bertills, Mathilda (2021)
Large carnivores, especially the African wild dog, Lycaon pictus, are vulnerable to human-mediated changes and climate effects. As they are apex predators, they also affect lower trophic levels. Due to anthropogenic land-use changes affecting habitat, prey, and population densities, large carnivore populations are declining. Thus, accurate population demographic estimates are required for conservation efforts to sustain carnivore populations. Genetic data are of high importance when analysing population demographics as they allow the study of oftentimes cryptic effects (loss of genetic diversity, inbreeding depression, and genetic drift). As next-generation sequencing techniques advance, genetic markers as single nucleotide polymorphism (SNP) can provide key ecological information. This information can be used to implement conservation efforts to impede the negative effects on populations. The aim of this study was to develop a highly informative SNP panel through de novo SNP discovery and genotyping in the non-modeled African wild dog. A total of 74 SNP markers were validated and 83 individuals were identified. The SNP chip provides a foundation for further research on relatedness, parental linkage, dispersal patterns, population size estimates, and the discovery of cryptic effects.